Genome-Wide Comparative Profiles of Triterpenoid Biosynthesis Genes in Ginseng and Pseudo Ginseng Medicinal Plants - Jing Lu (Life, 2023)
Saponin-rich medicinal plants, particularly ginseng and Pseudo ginseng, are valuable in traditional medical practice due to the presence of different saponins. These plants benefit from natural saponins/triterpenoids drugs, such as Ginsenosides, Gypenosides, Platycodins, and Lancemasides. Ginsenosides are highly required for research and functional materials preparation in industrial practices, and some compounds, like Compound-K, have been taken to human trials for various therapeutic applications. To elucidate the genes/transcripts profiles responsible for secondary metabolites and ginsenoside biosynthesis in Ginseng and Pseudo ginseng plant genomes, a comparative analysis was conducted in this study. Nine plant genomes with a 99% BUSCO completeness score were used, resulting in 49 KEGG secondary metabolite pathways, 571 cytochromes genes with 42 families, and 3529 carbohydrate genes with 103 superfamilies. The comparative analysis revealed 24 genes/transcripts belonging to the CYP716 family, which is involved in the ginsenoside biosynthesis pathway. Additionally, it found that various ginsenosides demonstrated strong binding affinity with twelve targets, with ginsenoside Rg3, Rg2, Rh1, Rh5, F3, Rh9, Panaxadione, Protopanaxatriol, Floral ginsenoside C, and Floral ginsenoside E exhibiting the highest binding affinities with the tested enzymes. Since these groups of enzymes are not yet fully characterized for Pseudo ginseng plants in the interconversion of triterpenoids, this comparative bioinformatics analysis could aid experimentalists in selecting and conducting characterization with practical knowledge.